Genotypic Sex and Severity of the Disease Determine the Time of Clinical Presentation in Steroid 17 alpha-Hydroxylase/17,20-Lyase Deficiency - BEREKET, ABDULLAH; DEMİRCİOĞLU, SERAP; GÜRAN, TÜLAY (KARGER, 2021)
Context: Steroid 17 alpha-hydroxylase/17,20-lyase deficiency (17OHD) is characterized by decreased sex steroids and cortisol, and excessive mineralocorticoid action. The clinical symptoms of hypocortisolemia are subtle. Aim: The clinical, biochemical, and molecular characteristics of patients with 17OHD were evaluated to determine the factors influencing the time of diagnosis and the management. Patients and Methods: Clinical data, steroid profiles by liquid chromatography-tandem mass spectrometry, and Sanger sequencing of the CYP17A1 gene was evaluated in 12 patients with 17OHD diagnosed between 2004 and 2020. Results: Median age of diagnosis was 13.9 (range: 0.04-29.5) years. Ten of 12 patients had 46,XY karyotype. Except for one boy with partial 17OHD, all patients had female external genitalia hence raised as females. The clinical presentation of 17OHD was earlier (median age: 7 years) in patients, who presented with severe hypertension, atypical genitalia, or positive family history (n = 6, 50%) than those without (median age: 15.3 years; p = 0.0005). The latter group presented with amenorrhea (n = 6, 50%). Steroid profile of patients uniformly showed a typical pattern of 17OHD regardless of the age at diagnosis. Serum gonadotropin concentrations were elevated in patients >12 years (n = 7), normal in pre-adolescents (n = 4), and low in a patient, who had a digenic inheritance of homozygous CYP17A1 and KISS1R mutations. Conclusions: Early clinical presentation and diagnosis in 17OHD are associated with symptomatic hypertension in both 46,XX and 46,XY patients or inadequate virilization of external genitalia in 46,XY partial 17OHD. In the absence of these, the clinical presentation is at late pubertal ages at which time amenorrhea and elevated gonadotropins are the hints for diagnosis.
Keywords: 17α -Hydroxylase deficiency; Hypertension; Primary amenorrhea; Absent puberty; Disorders; differences of sex development